Increasing Student’s Learning Motivation and Learning Outcomes through the Application of Participant Centered Learning (PCL) Cards - Santosa, Allicia Deana; Sartika, Sri Hardianti; Surgawati, Iis (Cakrawala: Jurnal Pendidikan, 2022)
The Covid-19 pandemic has had significant effects in many aspects, including the world of education. The changes require an adaptation to learning methods used increasing students learning motivation. In higher education, learning methods that are student centered and lecturers only serve to give instructions. Participant-centered learning (PCL) is a learning method that is suitable for use in higher education because collage students are considered participants not just students. The purpose of this research was to analyze the impact of implementing PCL in increasing motivation and learning outcomes. This research was conducted at the Management Study Program, Faculty of Economics, Siliwangi University with 94 collage students. The data sources used were the results of the pre-test and post-test using the Kahoot! learning platform and questionnaire data using the Materials Motivation Scale (IMMS), from the control and experimental groups. In the experimental class, learning was carried out using the PCL method, while in the control class, learning was carried out conventionally or teacher-centered learning (TCL). The results of the evaluation showed that the PCL class had an average score of 47% higher than the TCL, and students' learning motivation in PCL class is also about 40% higher than students in TCL class. So it can be concluded that there is a significant increase in terms of material understanding and student learning motivation with PCL method. The learning method of PCL can be adopted to be applied in learning in higher education.